2020
DOI: 10.1136/bmjopen-2020-039405
|View full text |Cite
|
Sign up to set email alerts
|

Associations of myeloperoxidase, interleukin-17A and heparin-binding EGF-like growth factor levels with in-stent restenosis after percutaneous coronary intervention: a single-centre case–control study in China

Abstract: ObjectivesTo investigate the changes in serum myeloperoxidase (MPO), interleukin (IL)-17A and heparin-binding EGF-like growth factor (HB-EGF) levels before and after percutaneous coronary intervention (PCI), and to evaluate the associations of MPO, IL-17A and HB-EGF levels with the 1-year restenosis rate.DesignCase–control study.SettingsXiangyang Central Hospital between January 2012 and December 2017.ParticipantsPatients with coronary heart disease who underwent PCI.InterventionsNot applicable.Primary and sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…These previous results revealed the role of CRP and TNF- α levels in predicting the risk of in-stent restenosis. However, Jiang et al [ 16 ] observed inflammatory factors at different time points during the perioperative period and found that serum hs-CRP and TNF- α increased 24 hours after coronary stent placement, but there was no obvious correlation with vascular restenosis within 6 months after surgery. This was also shown in this study, which may be caused by mechanical damage during stent placement, hypoxia, and the continuous extension of the stent to the vessel wall.…”
Section: Discussionmentioning
confidence: 99%
“…These previous results revealed the role of CRP and TNF- α levels in predicting the risk of in-stent restenosis. However, Jiang et al [ 16 ] observed inflammatory factors at different time points during the perioperative period and found that serum hs-CRP and TNF- α increased 24 hours after coronary stent placement, but there was no obvious correlation with vascular restenosis within 6 months after surgery. This was also shown in this study, which may be caused by mechanical damage during stent placement, hypoxia, and the continuous extension of the stent to the vessel wall.…”
Section: Discussionmentioning
confidence: 99%
“…PCI is the main treatment for CHD. [ 3 , 4 ] However, post-PCI restenosis remains a challenging clinical problem. [ 5 , 6 ] Restenosis is defined as a lumen occlusion of more than 50%.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Percutaneous coronary intervention is an effective technique for clinical treatment of coronary heart disease, and can greatly improve the survival rate of patients with coronary heart disease. [ 2 , 3 ] However, the problem of in-stent restenosis seriously influences the effect of percutaneous coronary intervention, which still perplexes clinical workers. [ 4 ] More than 98% non-protein coding RNA and nucleotides in human genome are long-stranded non-coding RNA (LncRNA) with more than 200 nucleotides that can regulate myocardial hypertrophy, myocardial fibrosis and cardiomyocyte apoptosis.…”
Section: Introductionmentioning
confidence: 99%